2021
DOI: 10.3389/fonc.2021.679348
|View full text |Cite|
|
Sign up to set email alerts
|

Downregulation of miR-135b-5p Suppresses Progression of Esophageal Cancer and Contributes to the Effect of Cisplatin

Abstract: Esophageal cancer (EC) is one of the commonest human cancers, which accompany high morbidity. MicroRNAs (miRNAs) play a pivotal role in various cancers, including EC. Our research aimed to reveal the function and mechanism of miR-135b-5p. Our research identified that miR-135b-5p was elevated in EC samples from TCGA database. Correspondingly real-time PCR assay also showed the miR-135b-5p is also higher expressed in Eca109, EC9706, KYSE150 cells than normal esophageal epithelial cells (Het-1A). CCK8, Edu, wound… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…MiR-135b-5p overexpression alleviated the impairment of proliferation, migration, and invasion and promoted apoptosis induced by H/R. Furthermore, we observed the opposite effects after knockdown of miR-135b-5p, which is consistent with previous findings [ 40 , 41 , 54 ]. These findings indicate that miR-135b-5p may affect PE progression by regulating trophoblast cell function.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…MiR-135b-5p overexpression alleviated the impairment of proliferation, migration, and invasion and promoted apoptosis induced by H/R. Furthermore, we observed the opposite effects after knockdown of miR-135b-5p, which is consistent with previous findings [ 40 , 41 , 54 ]. These findings indicate that miR-135b-5p may affect PE progression by regulating trophoblast cell function.…”
Section: Discussionsupporting
confidence: 92%
“…Another study has reported that the overexpression of miR-135b-5p promotes proliferation and reduces cell apoptosis by targeting Krüppel-like factor 4 in gastric cancer cells [ 54 ]. Conversely, miR-135b-5p knockdown suppresses proliferation and metastasis and facilitates the apoptosis of esophageal cancer cells via regulation of the thioredoxin-interacting protein (TXNIP) [ 40 ]. However, the role of miR-135b-5p in trophoblast function and PE has not been fully elucidated.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these two revealed to silence the same target genes. 71,72 These two miRNAs have recently been shown to have a critical role in carcinogenesis and invasiveness in lung, 73 breast, 74 gastric, esophageal, 75 and pancreatic. 51 cancers.…”
Section: Mir-27a and Mir-27bmentioning
confidence: 99%
“…MicroRNAs (miRNAs), containing 22 to 25 nucleotides, belong to single-stranded ribonucleic acid and exert function by degrading or inhibiting the translation of other proteins to regulate gene expression [ 7 ]. Dysregulation of miRNAs were closely associated with the occurrence of various diseases, especially cancers [ 8 12 ]. In lung cancer, miRNA-569 can be used as a tumor suppressor to induce apoptosis [ 13 ].…”
Section: Introductionmentioning
confidence: 99%